The Phantom of Bosnia-Herzegovina Revolt 1875-1878 (Journal of International Studies, 2020)
The Ottoman administration in Bosnia-Herzegovina which began in 1463 was based on Islamic laws. The local people accepted the Ottoman administration and had lived under its rule for 412 years. However, this was disrupted by a revolt in Bosnia in 1875 when Christian Slavs accused the government for maladministration and that the Christian welfare had been neglected. On this pretext the Serbians started a revolt. The Serbians were ambitious in wanting to annex Bosnia-Herzegovina as a part of Serbia 's territory and to create a Greater Serbia. This paper examines the role played by the Serbia in Bosnian revolt of 1875. The study is based on British documents.